Recent advances in air-battery chemistries. (June 2019) - Chawla, N.
Abstract: Lithium-ion batteries were first commercialized in the early 1990s and since then have been used for most of the electronic systems. Lithium-ion batteries have developed linearly over the past 25 years. However, the state-of-the-art commercial lithium-ion batteries have still not achieved the US Department of Energy's energy density target of 400 Wh kg −1.1 . With advancement of portable electronic devices and electrification of transportation rises a need for more advanced battery systems that can power these systems. Tremendous research is ongoing in new battery technologies to satisfy the energy storage requirements. Batteries with high energy density, long cycle life, and safe and low cost are the need of the hour. Metal-air batteries seem to be promising candidates for the future battery requirements because of their higher specific capacity and energy density as compared with lithium-ion batteries. In this article, I have discussed the various air battery chemistries and their recent developments.